How to Obtain an Australian Government Scholarship: A Community Service Presentation - Harits Masduqi (Amirul Bangun Bangsa, 2026)
In this article, the author discusses a community service activity in the form of a presentation on strategies for obtaining an Australian Government scholarship offered annually on the website https://www.australiaawardsindonesia.org. The presentation covered strategies for navigating the administration process and scholarship interviews. This half-day activity, which utilized presentations and a question-and-answer discussion, was held at a renowned private university and attended by 50 lecturers and high school teachers in Malang City. Overall, the community service activity was positively received by the participants. The committee also distributed several digital documents to encourage participants to apply for the scholarship managed by the AusAID in the future.